EDTECH: AN AI EDUCATIONAL MODEL FOR EMPOWERING FASHION DESIGN IDEATION – A CASE STUDY ON BABA NYONYA HERITAGE - Marzie Hatef, Jali (2026)
This paper introduces the AI Technology Integrated Education Model (EdTech) aimed at empowering fashion design ideation through the fusion of cultural heritage and advanced digital learning tools. Centred on the Peranakan Elegance Garment Design Challenge, which celebrates the rich heritage of the ethnic groups in Melaka, the research addresses the need for innovative, inclusive, and globally collaborative approaches in fashion education. The objective was to promote AI-enhanced e-learning, encourage collaboration among educators and students, and highlight impactful digital innovations in higher education. The methodology employed a case study approach, combining AI-assisted creative ideation tools, a curated cultural heritage repository, and a cloud-based collaborative learning platform. A group of fashion students engaged in a structured design process involving heritage research, AI-generated mood boards, storyboards, and real-time peer and mentor feedback. Data was collected through design output analysis and student feedback, measuring the effectiveness of AI integration in enhancing creativity. Findings indicate that AI-assisted ideation accelerated the creative process, improved the quality and originality of design outcomes, and enhanced students’ confidence in blending heritage motifs with contemporary fashion trends. Additionally, the cultural heritage repository supported the preservation and reinterpretation of Baba Nyonya traditions, demonstrating the potential of AI in safeguarding intangible heritage while inspiring innovative design. The study concludes that the AI technology-integrated education model is a viable and scalable solution for future-oriented fashion ideation and education. It bridges traditional craftsmanship and modern technology, supports inclusive participation, and fosters global collaboration. Beyond academia, the model holds potential for commercial applications in heritage-based product development and creative industries. This research contributes to the discourse on AI in innovative education, offering a replicable framework adaptable to various cultural and design contexts.